LABOR COST ACCOUNTING IN THE CONTEXT OF DIGITAL TRANSFORMATION: AUTOMATION AND ANALYTICAL APPROACHES - Abdumalik Abdiraximovich Tulyaganov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the improvement of labor cost accounting under conditions of digital transformation through automation and analytical approaches. A comparative analysis of traditional and automated accounting systems is conducted, highlighting the opportunities for real-time monitoring, coefficient-based evaluation, and the application of predictive analytical models. Special attention is given to the integration of ERP and HRM systems to enhance labor resource efficiency and optimize product cost. The findings demonstrate that the digitalization of labor cost accounting increases transparency, accuracy, and overall competitiveness of enterprises in a dynamic economic environment.